Predictive value of 10-year atherosclerotic cardiovascular disease risk equations from the China-PAR for new-onset lower extremity peripheral artery disease - He, Pengkang; Fan, Fangfang; Chen, Chuyun; Liu, Bo; Jia, Jia; Sun, Pengfei; Li, Jianping; Zhou, Jing; Zhang, Yan (Frontiers in Cardiovascular Medicine, 2022)
Lower extremity peripheral artery disease (LEPAD) is a common and serious health-threatening disease. This study aimed to evaluate the predictive value of 10-year atherosclerotic cardiovascular disease (ASCVD) risk equations from the China-PAR project (Prediction for ASCVD Risk in China) for incident lower extremity peripheral artery disease (LEPAD) after 6.75 ± 0.13 years of follow-up. A total 3595 Chinese participants without baseline ASCVD and LEPAD from an atherosclerosis cohort were enrolled in our study. The mean (interquartile range) baseline 10-year China-PAR ASCVD risk was 4.35 % (2.24%-8.44%), and the incidence of new onset LEPAD after 6.75 ± 0.13 years was 4.23%. In univariable logistic regression analysis, 10-year China-PAR ASCVD risk was significantly associated with LEPAD incidence (odds ratio [OR] for each 1% increase in the risk score = 1.06, 95% confidence interval [CI]: 1.03–1.08, P＜0.001). After adjusting confounders, the relationship remained significant (OR: 1.09, 95% CI: 1.05-1.1. P＜0.001). Participants with the highest risk (≥10%) had significant increased risk compared to those with the lowest risk (<5%) (OR=2.65, 95%CI: 1.15-6.07, P=0.022). Further interaction analyses showed no heterogeneity according to sex, age, BMI, smoking, drinking, hypertension, diabetes mellitus, dyslipidemia, renal function, waist circumference and family history. In conclusion, 10-year China-PAR ASCVD risk independently predicted the risk of new-onset LEPAD in a Chinese community-based population, indicating the importance of polyvascular diseases and the intrinsic interactions of its components.